Переобразуйте в многочлен стандартного вида:а)(6-4b)(2b+1)б)(x+x^2-1)(3-x)в)(c^2-c-1)(c^3+c+2)решите уравнение:(2x-2)(2x+3)-(4x+5)(x-3)=-1
Переобразуйте в многочлен стандартного вида:
а)(6-4b)(2b+1)
б)(x+x^2-1)(3-x)
в)(c^2-c-1)(c^3+c+2)
решите уравнение:
(2x-2)(2x+3)-(4x+5)(x-3)=-1
Ответ(ы) на вопрос:
Гость
а) 12b+6-8b^2-4b=-8b^2+8b+6 б) 3x^2-x^2+3x^2-x^3-3+x=-x^3+2x^2+4x-3 в) с^5+c^3+2c^2-c^4-c^2-2c-c^3-c-2=c^5-c^4+c^2-3c-2 Уравнение: (4x^2+6x-4x-6)-(4x^2-12x+5x-15)-1=0 4x^2+6x-4x-6-4x^2+12x+5x+15-1=0 19x+8=0 19х=-8 х=-8/19
Не нашли ответ?
Похожие вопросы